2006
DOI: 10.1007/s11746-006-5055-5
|View full text |Cite
|
Sign up to set email alerts
|

Flaking and extrusion as mechanical treatments for enzyme‐assisted aqueous extraction of oil from soybeans

Abstract: Flaking and extruding dehulled soybeans were evaluated as a means of enhancing oil extraction efficiency during enzyme-assisted aqueous processing of soybeans. Cellulase, protease, and their combination were evaluated for effectiveness in achieving high oil extraction recovery from extruded flakes. Aqueous extraction of extruded full-fat soy flakes gave 68% recovery of the total available oil without using enzymes. A 0.5% wt/wt protease treatment after flaking and extruding dehulled soybeans increased oil extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 15 publications
7
121
1
Order By: Relevance
“…It is not obvious based on these images why the addition of protease results in the increased release of oil. In the extruded material, however, the effect of protease is more pronounced, increasing yield from 68% to between 88% and 96% (1,8). Likewise, the extracted residual is drastically altered by the addition of protease ( Figure 4D).…”
Section: Microscopic Analysis Of Effects Of Comminution and Extractionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is not obvious based on these images why the addition of protease results in the increased release of oil. In the extruded material, however, the effect of protease is more pronounced, increasing yield from 68% to between 88% and 96% (1,8). Likewise, the extracted residual is drastically altered by the addition of protease ( Figure 4D).…”
Section: Microscopic Analysis Of Effects Of Comminution and Extractionmentioning
confidence: 97%
“…The use of protease and cellulase enzymes has also had significant effects on oil extraction yield from soy flours and extrudates in processes referred to as enzyme-assisted aqueous extraction processing (EAEP) (1,6,8,9). In soy, there is an association between protein solubility and oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Thermomechanical processing can be used to modify the structure of plant materials to obtain better separation or extractability of proteins (11,23,35). There are not many published studies on the effects of thermomechanical treatment of wheat and rice brans.…”
Section: Fractionation and Extraction Of Proteins From Cereal Side-stmentioning
confidence: 99%
“…Proteases improved oil extraction from both soybean flour and extruded soybean flakes, but combining extrusion with enzyme treatments yielded more free oil than enzyme treating flour alone W.-G. Zhang 32 (Lamsal, et al, 2006). Enzyme-assisted aqueous extraction processing (EAEP) of extruded flakes yielded the highest oil yield, which were 96% for soybean (De Moura, et al, 2008;Wu, et al, 2009).…”
Section: Industrial Processes For the Extraction Of Edible Oil Frommentioning
confidence: 99%
“…In order to effectively increase the oil yield, some pretreatment approaches have been utilized based on aqueous enzymatic oil extraction. Sharma et al (2006) reported that the ultrasonic pre-irradiation enhanced the oil yield from 77%to 95% (w/w) using aqueous enzymatic oil extraction from almond.Proteases improved oil extraction from both soybean flour and extruded soybean flakes, but combining extrusion with enzyme treatments yielded more free oil than enzyme treating flour alone Lamsal, et al, 2006). Enzyme-assisted aqueous extraction processing (EAEP) of extruded flakes yielded the highest oil yield, which were 96% for soybean (De Moura, et al, 2008;Wu, et al, 2009).…”
mentioning
confidence: 99%